(untitled) (International Journal of Engineering and Computer Science, 2015)
The task of web mining is to classify documents automatically many algorithms have been developed to deal with automatic text classification The most common techniques used for this purpose include Apriori algorithm. In this survey, the various models using Apriori algorithm are explained to classify the text of documents, saving time and increasing accuracy of the web searching. It increases the data accessibility on the web giving the results faster. All the methods explained in this survey are executed to get the result accuracy for retrieving the web pages faster and getting the documents classified easily based on the probability calculated. The easiest algorithm used for classification of documents is Apriori algorithm used. The result of the survey of various methods used for classification shows that the search results are classified according to the classes they belong to. It is done on the basis of content matching of documents.